2017
DOI: 10.1111/jvh.12708
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world experience with the all‐oral, interferon‐free regimen of ombitasvir/paritaprevir/ritonavir and dasabuvir for the treatment of chronic hepatitis C virus infection in the German Hepatitis C Registry

Abstract: Real-world studies are relevant to complement clinical trials on novel antiviral therapies against chronic hepatitis C; however, clinical practice data are currently limited. This study investigated effectiveness and safety of ombitasvir/paritaprevir/ritonavir (OBV/PTV/r)±dasabuvir (DSV)±ribavirin (RBV) for treatment of HCV genotype (GT) 1 and GT4 infection in a large real-world cohort. The German Hepatitis C Registry is an observational cohort study prospectively collecting clinical practice data on direct-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
33
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 24 publications
14
33
0
1
Order By: Relevance
“…At week 4 of treatment, the rate of serum HCV RNA level < LLOQ in our patients receiving PrOD‐based regimens was 98.0%, which was much higher than East Asian HCV‐1b patients receiving peginterferon plus RBV. After 12 weeks of off‐therapy follow‐up, the SVR 12 rate in our study was 98.1% and was comparable with the clinical trials and the published real‐world studies for HCV‐1b infected patients receiving the PrOD‐based regimens . In lines with the trial reports, we confirmed that the SVR 12 rates were comparable in our patients receiving PrOD‐based treatment, regardless of sex, age, prior treatment experience, HBsAg status, RBV usage, baseline HCV RNA levels, eGFR or stage of hepatic fibrosis .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At week 4 of treatment, the rate of serum HCV RNA level < LLOQ in our patients receiving PrOD‐based regimens was 98.0%, which was much higher than East Asian HCV‐1b patients receiving peginterferon plus RBV. After 12 weeks of off‐therapy follow‐up, the SVR 12 rate in our study was 98.1% and was comparable with the clinical trials and the published real‐world studies for HCV‐1b infected patients receiving the PrOD‐based regimens . In lines with the trial reports, we confirmed that the SVR 12 rates were comparable in our patients receiving PrOD‐based treatment, regardless of sex, age, prior treatment experience, HBsAg status, RBV usage, baseline HCV RNA levels, eGFR or stage of hepatic fibrosis .…”
Section: Discussionsupporting
confidence: 89%
“…Following the clinical trials reporting excellent efficacy and safety profiles, the real‐world data in Western HCV‐1b patients receiving PrOD with or without RBV for 12 weeks showed that the SVR 12 rates range from 87.6% to 98.9% . Regarding the real‐world data of PrOD‐based treatment in Asian patients, one report from Hong Kong evaluated 35 HCV‐1b patients receiving PrOD with or without RBV for 12–24 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Real‐world data show that patients with kidney disease have a good virological response with DAAs. SVR12 rates were high in a cohort study evaluating ombitasvir/paritaprevir/ritonavir ± dasabuvir ± ribavirin in patients with HCV genotype 1 and 4 infection, and all patients with moderate‐to‐severe renal impairment achieved an SVR (100%, n = 34/34) . Furthermore, the SVR12 rate was excellent (100% n = 19/19) in a small study in patients with end‐stage renal disease on hemodialysis and with HCV genotype 1 infection who received ledipasvir and sofosbuvir on alternate days for 12 weeks …”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 47%
“…Furthermore, an SVR rate of 97% (170/176) was reported in a subset of more difficult patients (genotype 1b with cirrhosis) . Real‐world data from Germany, Spain and Israel have also reported high SVR rates of 96% (n = 892), 96.8% (n = 1567) and 98.8% (n = 416), respectively in patients with genotype‐1 infection receiving this regimen . In the German cohort, analysis of response across subgroups showed consistently high SVR rates: 95% in patients with cirrhosis (n = 123/129), 100% in those with moderate to severe renal impairment (n = 34/34) and 96% in subgroups that are usually excluded from clinical trials (including patients ≥70 years old [n = 64/67] and prior failures to protease inhibitor treatment [n = 46/48]).…”
Section: Efficacy In the Real‐world Settingmentioning
confidence: 91%
See 1 more Smart Citation